2022
DOI: 10.1097/aud.0000000000001257
|View full text |Cite
|
Sign up to set email alerts
|

Psychologically Informed Practice in Audiological Rehabilitation: Audiologist Perceived Barriers, Facilitators, and Preparedness

Abstract: Objectives: Psychological factors, such as mental illness, mental health, attitudes, emotions, and coping styles, are known to impact the success of audiological rehabilitation. However, evidence suggests that audiologists are not sufficiently addressing client psychological factors. Psychologically informed practice, implemented in other healthcare professions, is a framework that guides clinicians in addressing both the physical and psychological factors of a condition throughout rehabilitation. Psychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 80 publications
2
6
0
Order By: Relevance
“…All participants indicated that they believed at least some patients would benefit from referral to a professional specializing in psychosocial care and that intervention would be beneficial. This aligns with prior evidence suggesting audiologists have positive attitudes toward psychosocial intervention in pediatric ( 23 ) and adult ( 39 , 44 , 47 , 48 ) audiological care. Audiologists recognize their role in psychosocial care ( 23 , 43 ), and express interest developing knowledge and skills required to appropriately address mental health needs among their patients ( 44 , 48 ).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…All participants indicated that they believed at least some patients would benefit from referral to a professional specializing in psychosocial care and that intervention would be beneficial. This aligns with prior evidence suggesting audiologists have positive attitudes toward psychosocial intervention in pediatric ( 23 ) and adult ( 39 , 44 , 47 , 48 ) audiological care. Audiologists recognize their role in psychosocial care ( 23 , 43 ), and express interest developing knowledge and skills required to appropriately address mental health needs among their patients ( 44 , 48 ).…”
Section: Discussionsupporting
confidence: 86%
“…Specific feedback indicated that the respondents were comfortable with the screeners, and they appreciated the audiologists inquiring about their mental health. Findings from this study are comparable to those of other studies in which audiologists reported not to regularly use mental health screeners or other structured questionnaires as a part of clinical practice ( 39 , 48 ). The use of mental health screeners would take the burden of initiating concerns related to psychosocial health of the patient and allow audiologists to guide counseling in a way that these concerns are addressed.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations